Decolonization and development - "Paranjape, Makarand" (New Delhi, 1993)
this book creates a forum for a neo-Ghandian perspective in current debates on decolonization and development. The author defines India as a space for plurality and tradition which offers an alternative to the western ways. He asserts that decolonization means the protection and continuation of Indian ways of thinking and of perceiving and experiencing reality. At the same time however, he believes that the rejection of the West would be both impossible and undesirable. What is needed is a creative strategy for assimilating outside influences.
Keywords: India-Politics and government